From the editors - Esterhuyse, Abel; Liebenberg, Ian (Scientia Militaria - South African Journal of Military Studies, 2014)
This issue of Scientia Militaria brings an interesting mix of articles and book reviews that deal with the spectrum of defence, strategy, human security matters, civil–military relations, conflict and conflict resolution, peacekeeping and the history of war. Also included are articles from the natural sciences and an exploration of moments in South Africa’s history of conflict. Geography and war, battle space and nature also receive attention. In short, we carry contributions from the social sciences, geography, military history and the natural sciences, which all demonstrate Scientia Militaria’s commitment to multi- and interdisciplinary approaches.